Pendekatan Pedagogi Transformatif Dalam Pembelajaran Sosial Emosional (SEL) Sebagai Upaya Menumbuhkan Resiliensi dan Belas Kasih Siswa Kristen - Didik Sulistyoadi; Ester Lusy Andayani (Teokristi: Jurnal Teologi Kontekstual dan Pelayanan Kristiani, 2026)
The development of technology and information has caused disruption to the lives of Christian students. Behind the positive impacts of that development, negative influences also emerged, leading students' lives toward individualism, a lack of empathy, and a fragile mentality. This poses a significant challenge for contemporary Christian education in its efforts to achieve its goal of shaping resilient and compassionate students. Christian education requires the right learning approaches and strategies to address this situation. The Transformative Pedagogical approach implemented in Social Emotional Learning (SEL) is the best alternative for Christian Education in the current context. This research was conducted using a literature review, which involved a theoretical analysis of the thoughts of experts to analyze and draw conclusions. This research found that by integrating transformative pedagogical approaches into SEL learning, students have the potential to be successfully guided to fully understand themselves, others, and God. This actively leads them to become resilient individuals, strong in facing life's dynamics, and compassionate.